Are we failing to “build on the scientific basis of medicine?” - Coderre, Sylvain; Ripstein, Ira; Veale, Pamela; Mclaughlin, Kevin (Canadian Medical Education Journal, 2018)
In this article, we question if and why the Canadian national medical education organizations have failed to introduce or promote changes that compel or encourage Canadian medical schools to heed the recommendation from the Future of Medical Education in Canada report to "build on the scientific basis of medicine." We end by offering suggestions on how these organizations could help Canadian medical schools build in the scientific basis of medicine.